(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2020)
The city’s thermal environment plays an important role in achieving comfort and quality of life, especially during the current global pandemic. Meanwhile, reduction in the green areas has been observed to be continuously causing climate change in cities and one of the proposed solutions to this is by developing a greening system for buildings. This paper, therefore, assessed the ability of vertical garden to decrease air and surface temperatures as well as CO2 levels. The research involved field measurements of these parameters both inside and outside the building along with the modification of the vertical garden distance at 0.5 m and 1 m as well as the plant type including red spinach or amaranthus hybridus, mustard or brassica juncea, celery or apium graveolens linn, and cat’s whiskers or orthosiphon spicatus. The results showed an average decrease of 0.75°C in air temperature, 16.4ºC in surface temperature, and 58.8 ppm in CO2 levels. Moreover, a maximum reduction of 6ºC was achieved in air temperature with red spinach plants at 0.5 m, 26.3ºC in surface temperature by the Rred spinach plant, and 124 ppm in CO2 levels by celery plants. In conclusion, a closer distance and darker color of the leaves as well as the red spinach species were found to be the main consideration in the application of vertical gardens in urban homes due to their ability to reduce the temperature on the limited land. © 2020 Agung Murti Nugroho